How Digital Leadership Enhances Employee Creativity: The Mediating Roles of Digital Culture, Employee Digital Capability, and Innovation Self-Efficacy in Indonesian Startups - Putri Aulia Setiadi; Ika Nurul Qamari (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the relationship between Digital Leadership and Employee Creativity through the mediating roles of Digital Culture, Employee Digital Capability, and Employees’ Innovation Self-Efficacy in Indonesian startup companies. Design/methodology/approach – This study employed a quantitative cross-sectional design using survey data collected from 171 employees working in Indonesian startup companies. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results – This research demonstrates that Digital Leadership is positively and significantly related to perceived Digital Culture, Employee Digital Capability, and Employee Innovation Self-Efficacy. However, only perceived Digital Culture is positively and significantly related to Employee Creativity. Of the seven hypotheses proposed, three were not supported. Therefore, this research highlights factors that may not support Employee Creativity. A more detailed discussion is provided in the results and discussion section. Originality/Value – This study extends the models of Yang et al. (2025) and Shin, Mollah, & Choi, 2023) by integrating three theoretically distinct employee-level mechanisms into a parallel mediation model linking Digital Leadership to Employee Creativity. Using the individual as the unit of analysis, this study provides a contextual and theoretical extension of previous digital leadership research. The findings identify Perceived Digital Culture as the only significant mediating pathway.